Analysis of Impacted Mandibular Second Premolar Finding Trough Panoramic Radiograph: A Case Report - Arsyad, Muhammad A.; Muchlis, Muhammad R. E. (Universitas Sam Ratulangi, 2025)
Abstract: An impacted tooth is a tooth that cannot erupt to its normal functional position after the development of the root. The mandibular second premolar is the third most impacted that can potentially cause problems in the tooth and surrounding structures. Panoramic radiography can detect and evaluate the impacted tooth, surrounding tissues, and possible pathologies including cysts and tumors. This study aimed to discuss the findings of impacted mandibular second premolar on panoramic radiograph. We reported a 13-year-old male patient who came to RSIGMP-UMI complaining of protruding upper front teeth and occasional food impaction in the right lower anterior molar area. Panoramic radiograph showed a vertical angulation of tooth 45, with the crown directed towards the occlusal line between teeth 46 and 44, and the apex directed towards the mandibular ramus border approaching the mandibular canal, with an inclination 0° and type I. Panoramic radiographs are essential in dentistry, particularly in orthodontic treatment. In this case, the radiograph revealed an impacted mandibular second premolar. Extraction of this tooth is often necessary for optimal treatment outcomes. However, in this case, the patient's parents were still hesitant to proceed with tooth extraction. Keywords: impacted teeth; second premolar teeth; panoramic radiography